Behavior Analysis of Highway Rigid Pavement on Clay Soil with Beam on Elastic Foundation Approach - Srikandi, I Gusti Ayu Santi; Sangadji, Senot; Purwana, Yusep Muslih (International Journal of Membrane Science and Technology, 2023)
An important consideration in designing road infrastructure is the study of the behavior of rigid pavement structures and subsurface soils. Vehicle loads received by the rigid pavement are transferred to the soil which provides the required response and bearing capacity. To examine this problem the beam on elastic foundation (BoEF) approach can be used. The purpose of this research is to identify and assess the relationship between pavement stiffness and the soil that supports it. The object of this research is Solo Yogyakarta - NYIA Kulonprogo Toll Road section 1 STA 2+949 to STA 2+973. The pavement is modeled as a finite element resting on a series of springs that represent the characteristics of the subgrade soil. The structural analysis results show that the pavement should be designed with appropriate thickness and sufficient elastic modulus to withstand various traffic loads. In addition, an understanding of pavement deformation and soil response to loads is essential in minimizing road damage.